Acidic Dissociation of Diprotonated Piperazine in Methanol-Water Solvents From 10 to 40 °C - Paabo, Maya (J Res Natl Bur Stand A Phys Chem, 1970)
The first dissociation constant of piperazinium ion has been determined by the emf method in five methanol-water solvents (10 to 70 wt % MeOH) at 25 °C and in three solvents (10, 20, and 50 wt % MeOH) from 10 to 40 °C. From the variation of the dissociation constant with temperature, the changes of enthalpy, entropy, and heat capacity were derived and compared with similar data for piperazinium ion in water. The variation of pK, ΔS°, and [Formula: see text] have been used to interpret the effect of the double positive charge on the solute-solvent interactions as compared to the effect exhibited by a single positive or a negative charge.